Ocenjevanje somatosenzoričnega sistema - Rodi, Zoran (Rehabilitacija (Ljubljana), 2012)
Methods for assessing the somatosensory system are overviewed. Emphasis is puton clinical tests, and neurophysiological methods (peripheral nerve conduction studies, somatosensory evoked potentials, microneurography, nociceptive reflexes, laser-evoked potentials).
Keywords: Clinical Laboratory Techniques; clinical tests; diagnostika; klinične laboratorijske tehnike; klinični testi; laboratorijske preiskave; laboratory examinations; Neurology; neurophysiological methods; nevrofiziološke metode; nevrologija; somatosensory system; somatosenzorični sistem